1972
DOI: 10.1111/j.1365-2222.1972.tb01292.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of skin, nasal and inhalation tests with the IgE in the serum, nasal fluid and sputum

Abstract: In the course of developing a planned treatment by hyposensitization, still undergoing clinical trials, a system was devised which might be used in assessing respiratory allergies. The sensitivity of the patient assessed by skin, topical nasal instillation and inhalation tests was related to the appearance of IgE-staining cells in the nasal secretion and sputum after a successful challenge test, and the correlation of IgE in the serum and nasal fluid.The presence of increased eosinophil cell content and the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1974
1974
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…IgE antibodies have a central role in allergic disease, with elevated levels of both total and allergen-specific IgE in serum of atopic patients [1,2]. This is frequently paralleled by high levels of total and allergen-specific IgG4 [3].…”
Section: Introductionmentioning
confidence: 99%
“…IgE antibodies have a central role in allergic disease, with elevated levels of both total and allergen-specific IgE in serum of atopic patients [1,2]. This is frequently paralleled by high levels of total and allergen-specific IgG4 [3].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, only patients who were demonstrated to have positive skin reactions to solutions of D. pteronyssinus were included. The correlation, however, between skin test reactions and other tests of hypersensitivity is not complete (Gronemeyer and Fuchs, 1959; Houri et al 1972; Aas, 1970). However, no other skin tests were undertaken in the majority of these patients, who may therefore have multiple sensitivities.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that antigen‐specific IgE can be produced in the sinonasal mucosa of people with seasonal and perennial allergic rhinitis (AR), and increases rapidly in the epithelium and nasal secretions of people with AR who are challenged with an antigen to which they are sensitized . It has also been demonstrated that locally‐produced IgE can be present in nasal secretions even though skin testing and in vitro testing are negative. Based on these findings, it has been suggested that people diagnosed with idiopathic NAR may actually have allergic sensitization exclusively in the local region where symptoms are most active.…”
mentioning
confidence: 99%